An unusual case of pedunculated subserosal leiomyosarcoma of the uterus mimicking ovarian carcinoma. Issue 1 (December 2016) - Suh, Dong; Kim, Yoon; Yun, Ka; Lee, Nam; Choi, Kyung; Kim, Ki; Yoon, Man
Abstract Background Leiomyosarcoma of the uterus is an extremely rare but highly aggressive tumor that accounts for only 1–2 % of uterine malignancies, and is usually associated with a dismal outcome. Case presentation The authors present an unusual case of pedunculated subserosal leiomyosarcoma of the uterus mimicking ovarian carcinoma. A 57-year-old postmenopausal woman presented with progressive low abdominal pain and urinary frequency. Pelvic magnetic resonance imaging revealed a large adnexal mass with carcinomatosis peritonei. Laboratory examination revealed an elevated serum CA-125 level (398.4 U/ml). The patient underwent exploratory laparotomy under suspicion of ovarian malignancy. Frozen section indicated malignancy originating from the uterus, and thus, total abdominal hysterectomy, bilateral salpingo-oophorectomy, omentectomy, pelvic and para-aortic lymph node dissection, and mass excision were performed. Subsequent histopathologic examination resulted in a final diagnosis of leiomyosarcoma of the uterus. The patient's postoperative course was uneventful, and gemcitabine and docetaxel adjuvant chemotherapy was administered. Conclusion The authors report an unusual case of pedunculated subserosal leiomyosarcoma of the uterus mimicking ovarian carcinoma.